Analisis Peran Bank Syariah dalam Mendukung Perekonomian Desa di Bojonegoro - Fahmi , Moh Dhofir Jenny Al (Journal of Islamic Finance and Syariah Banking, 2024)
This study examines the influence of Syariah Bank on the rural economy in Bojonegoro through a literature review. The review compiles data on Syariah Bank's contributions to rural economic growth, with an emphasis on financial accessibility and empowerment aligned with Syariah principles. The findings reveal that Syariah Bank significantly enhances community welfare and stimulates local economic progress by offering financial services rooted in ethical values and justice. These banks play a crucial role in overcoming major issues faced by local farmers, such as limited capital, technology, and market access. Through inclusive financial services, Syariah Bank helps farmers boost their productivity and increase the value of their agricultural products. Moreover, the research shows that Syariah Bank generates new business opportunities for village communities, thereby bolstering the local economy. The adherence to Syariah principles in their operations ensures transparency and fairness in financial dealings, thereby enhancing public trust in these institutions. This study contributes to a deeper understanding of how Syariah-based financial institutions can effectively strengthen the rural economy in Bojonegoro, fostering more inclusive and sustainable opportunities for residents. The findings are intended to inform policy decisions that further support rural economic development through Syariah-compliant financial approaches.